Inovações tecnológicas na elaboração de carne de sol - Campêlo, Maria Carla da Silva (Universidade Federal Rural do Semi-Árido, 2019)
Meat and meat products have a prominent place in human nutrition because of the high levels of protein, essential amino acids and nutrients that enrich the diet of consumers. Sun-dried meat, a characteristic product of the Brazilian northeast, is known to be a lightly salted food, partially dehydrated and semi preserved by salting. However, this food does not have technical regulations that standardize its production, especially the percentage of addition of salt, being manufactured exclusively by hand, with great divergence in microbiological, physical-chemical and sensory characteristics. In this way, the objective was to evaluate the interference of the NaCl content variation in the use of active packaging and modified atmospheres in the quality of sun-dried meat. Therefore, the present study consisted of four distinct and complementary experiments, being them: Experiment I: Useful life and consumer preference for sun-dried meat produced with different levels of NaCl; Experiment II: Extension of the useful life of sundried meat packed in different atmospheres; Experiment III: Sensory profile of sun-dried meat with herbal salt and Experiment IV: Sun-dried meat packed with active coatings. Sun-dried meat with 2.5% NaCl showed positive changes in physical-chemical characteristics, greater acceptance and purchase intention by tasters. The alteration of the atmosphere of the sun meat packaging with CO2 and N2 promoted the increase of the shelf life. The active coatings made with basil and rosemary extracts provided better conservation of the quality parameters, in addition to promoting improvements in the length and spacing of the sun-dried meat fibers. The reduction in NaCl content associated with the introduction of natural preservatives, active coatings and modified atmosphere may add economic benefits to sunflower meat.
Keywords: Conservantes naturais; Carne salgada; Perfil sensorial; Qualidade microbiológica; Filmes Ativos; Natural preservatives; Salted meat; Sensory profile; Microbiological quality; Active Films; CIENCIAS AGRARIAS::MEDICINA VETERINARIA